Strategi Pemasaran dalam Menarik Minat Konsumen pada Suria City Hotel Syariah Bandung - Risma Helmaya Putri; Deden Heri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
A marketing strategy is a plan designed and implemented by an organization to achieve marketing objectives. It involves the use of various methods, tools and techniques to promote a product or service to a target market, build a brand, and increase sales. In this case, consumer interest is the key to success in marketing a product or service. Interested consumers will be more likely to buy and maintain a relationship with the company. Therefore it is important for companies to have and improve effective marketing strategies to attract consumers. The purpose of this study is in line with the author's intention to know the effectiveness of the marketing strategy that has been implemented by Suria City Hotel Syariah by using the 4 P marketing model (product, price, place, promotion) and provide recommendations to streamline marketing strategies so that consumers can know and be interested in Suria City Hotel Syariah services. The method used in this study is qualitative descriptive by means of purpose sampling, namely selecting resource persons according to research needs, using primary data sources obtained from observations, interviews, and documentation as well as secondary data sources obtained from books, journals, theses, official websites, and other references in accordance with the research. The result of this study is that the marketing strategy carried out by Suria City Hotel Syariah is to provide a variety of superior products even though currently some of its products have not been able to operate again after the pandemic. The price offered is quite affordable for all circles. The location strategy is quite strategic because it is in the middle of the city. Then the promotion carried out by Suria Hotel only uses the website, facebook and Instagram, it was not managed properly. Therefore the author provides recommendations to overcome these problems, namely by implementing a promotion mix ( advertising) such as advertising ( advertising) , individual sales (personal selling), sales promotion ( sales promotion), Direct Sales ( Direct Marketing). Word of mouth).